2001
DOI: 10.1038/ni0901-882
|View full text |Cite
|
Sign up to set email alerts
|

Inducible IL-2 production by dendritic cells revealed by global gene expression analysis

Abstract: Dendritic cells (DCs) are strong activators of primary T cell responses. Their priming ability is acquired upon encounter with maturation stimuli. To identify the genes that are differentially expressed upon maturation induced by exposure to Gram-negative bacteria, a kinetic study of DC gene expression was done with microarrays representing 11,000 genes and ESTs (expressed sequence tags). Approximately 3000 differentially expressed transcripts were identified. We found that functional interleukin 2 (IL-2) mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
272
4
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 449 publications
(293 citation statements)
references
References 32 publications
13
272
4
4
Order By: Relevance
“…It has been shown that Bcl-2 is rapidly down-regulated upon the induction of DC maturation (24). In addition, CD40 ligand, RANK ligand, TNF-␣, IL-12, IL-15, LPS, and CpG were shown to inhibit apoptosis in DCs via up-regulations of Bcl-2, Bcl-x L , and cellular inhibitor of apoptosis proteins (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Bcl-2 is rapidly down-regulated upon the induction of DC maturation (24). In addition, CD40 ligand, RANK ligand, TNF-␣, IL-12, IL-15, LPS, and CpG were shown to inhibit apoptosis in DCs via up-regulations of Bcl-2, Bcl-x L , and cellular inhibitor of apoptosis proteins (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis was done by hybridizing the fragmented cRNAs to the Affymetrix GeneChip® Yeast Genome S98 array, which permits the monitoring of the mRNA abundance from 6400 ORFs. Probe array hybridizations were carried out under rotation at 45°C for 16 h as described (35). The arrays, stained by incubation with 2 g/ml phycoerythrin-streptavidin (Molecular Probes, Eugene, OR) and 1 mg/ml acetylated bovine serum albumin (Sigma), were read at a resolution of 7.5 m by a confocal scanner and analyzed with the MicroArray Suite 4.0 Gene Expression analysis program (both from Affymetrix).…”
Section: Methodsmentioning
confidence: 99%
“…Cell activation triggered by the interaction of PAMPs and TLRs is characterized by induction of host defense genes, production of both proinflammatory and anti-inflammatory regulatory cytokines, and the up-regulation of cell surface markers (3)(4)(5)(6)(7)(8)(9). Several bacterial PAMPs have been identified, including bacterial DNA.…”
mentioning
confidence: 99%